2014
DOI: 10.1007/978-3-319-08072-7_42
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Movement Intention from Movement-Related Cortical Potentials with Different Paradigms

Abstract: Abstract. In this study, we compared the effects of two imagery paradigms typically used within the field of brain computer interfaces on the detection of movement intention from scalp electroencephalography (EEG). This issue is important in the rehabilitation area because of its direct relation with appropriately timed neurofeedback. Subjects were asked to imagine hand or foot movements using either a random or a non-random cue. Templates were constructed individually for each subject. Movement intent was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Indeed this is what we found and it is likely associated to the greater MRCP variability when attention is drifted ( Figure 5). As demonstrated in previous studies, signal variability is an indicator of movement preparation processes (Aliakbaryhosseinabadi et al, 2014;Jiang et al, 2015 ) and it is likely that these are most affected by the alterations in user attention.…”
Section: Bci For Neuromodulationmentioning
confidence: 64%
See 1 more Smart Citation
“…Indeed this is what we found and it is likely associated to the greater MRCP variability when attention is drifted ( Figure 5). As demonstrated in previous studies, signal variability is an indicator of movement preparation processes (Aliakbaryhosseinabadi et al, 2014;Jiang et al, 2015 ) and it is likely that these are most affected by the alterations in user attention.…”
Section: Bci For Neuromodulationmentioning
confidence: 64%
“…In our previous studies we have demonstrated that Cz is the superior channel for detection (Aliakbaryhosseinabadi et al, 2014) of simple dorsiflexion, so Cz was used as the channel for movement analysis (Aliakbaryhosseinabadi et al, 2014;Xu et al, 2014). In addition, the large Laplacian of Cz was calculated with a linear combination of surrounding channels where each channel has a fixed coefficient as indicated in equation 1:…”
Section: Mrcp Analysismentioning
confidence: 99%